2005
DOI: 10.1071/ap05044
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of aMycosphaerella crypticapopulation

Abstract: We studied the genetic structure of Mycosphaerella cryptica following natural infection of Eucalyptus globulus in a genetic trial. Results from this study indicated significant genetic variation within, and between, E. globulus families (three cloned and control-crossed F 2 and four open-pollinated families). Single-ascospore isolates were sampled from 72 E. globulus trees with contrasting levels of resistance within the trial, 21 E. nitens trees in an adjacent plantation, and five distant Eucalyptus plantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…Quantitative genetic studies have reported genetic variation in the susceptibility of E. globulus to MLD, both within and between provenances (Carnegie et al 1994;Dungey et al 1997;Milgate et al 2005a,b) as well as within segregating families (Milgate et al 2005a). There is some evidence for a positive correlation between resistance to the disease and rainfall, consistent with more intense natural selection for disease resistance in high-rainfall areas (Carnegie et al 1994;Dungey et al 1997).…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Quantitative genetic studies have reported genetic variation in the susceptibility of E. globulus to MLD, both within and between provenances (Carnegie et al 1994;Dungey et al 1997;Milgate et al 2005a,b) as well as within segregating families (Milgate et al 2005a). There is some evidence for a positive correlation between resistance to the disease and rainfall, consistent with more intense natural selection for disease resistance in high-rainfall areas (Carnegie et al 1994;Dungey et al 1997).…”
mentioning
confidence: 60%
“…The three controlled-cross families were planted in a field trial at Woolnorth in northwest Tasmania (Figure 1) in May 1998, as part of an experiment also containing open-pollinated families collected from four of the grandparents (KI2, KI5, T7, T5; see Milgate et al 2005a for a full description of the trial design). The trial featured an incomplete block design, consisting of two replicates, each with 20 incomplete blocks of 30 or 36 trees.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Freeman et al (2008) and Milgate et al (2005b) suggest that a gene-for-gene relationship may exist between pathogen and host in this pathosystem. Freeman et al (2008) identified two major QTL (quantitative trait loci) for resistance to T. cryptica, one of which was validated in an additional E. globulus family and the second across two additional families, and Milgate et al (2005b) identified a T. cryptica biotype only associated with resistant host genotypes. This association is further complicated by the potential for multiple mechanisms of resistance, tolerance and/ or avoidance, which are at play in the relationship between the host and pathogen (Rausher, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Eucalyptus spp. are generally more susceptible to infection by Mycosphaerella and Teratosphaeria species during their juvenile leaf phase and the leaf infections caused by these fungi reduce the photosynthetic capacity, leading to premature defoliation and stunting of growth (Park and Keane 1982b;Lundquist and Purnell 1987;Carnegie and Ades 2003;Milgate et al 2005b;Pinkard and Mohammed 2006).…”
Section: Comparison Of Mycosphaerella and Teratosphaeria Diseasesmentioning
confidence: 99%